An in vitro and in vivo study of plasma treatment effects on oral biofilms. Issue 1 (1st January 2019) - Hong, Qing; Dong, Xiaoqing; Chen, Meng; Sun, Hongmin; Hong, Liang; Wang, Yong; Li, Hao; Yu, Qingsong
ABSTRACT: Management of dental plaque/biofilms is critical to maintain oral health. The objective of this study is to investigate the treatment effects of non-thermal atmospheric gas plasmas on oral biofilm formation and recovery under in vitro and in vivo conditions. Streptococcus mutans biofilms, a significant contributor to tooth decay, were cultured and treated by plasma. It was found that plasma treatment not only significantly reduced the in vitro biofilms, but also increased the metabolic activity of the bacteria in the biofilms. As compared with untreated control group, the cell metabolic activity, as measured by MTT assay, increased by 273%, and the aconitase activity increased by 446% for the plasma-treated group. The increased metabolic activity of the plasma-treated biofilm bacteria enhanced their susceptibility to antibiotic and host defense. An in vivo animal model using a total of 60 female rats (19 days old) were used to evaluate the anti-caries effects on the molars by 2 min of plasma treatment. It was found that, 6 months after the plasma treatment, the decayed surfaces were reduced by 62.5% on the upper molars and by 31.6% on the lower molars as compared with the untreated upper and lower molars, respectively. These in vitro and in vivo data demonstrate that the physiological state change of the biofilm due to plasma treatment provided benefit to caries control and prevention.